Edisi 1 Vol 2 September 2023 MEMBANGUN UMAT DENGAN ZAKAT: STRATEGI FUNDRAISING MELALUI PROGRAM KALENG SEDEKAH DAN SEDEKAH RAMADHAN - nidhom, Misbahun (PRODI ES SEKOLAH TINGGI ISLAM KENDAL, 2023)
Paying zakat, infaq and shadaqah is a real step tobuilding social synergy that can be developed in the context of modern life,The increasing number of government-owned zakat agencies or institutionsor belonging to a particular organization, there needs to be outreach to the public andprofessionalism of an institution in mobilizing and managing zakat and infaq fundsand shodaqoh. The mandate from donors to amil zakat institutions is partThe most important thing is to increase donors' trust in the zakat amil institutionin other words muzakki, munfiq, and mushoddiq must be positioned as determinantsthe growth and development of amil zakat institutions, because it is impossible for an amil zakat institutionZakat can survive without the presence of muzakki, munfiq and mushoddiq. NU through the InstituteZakat, Infaq and Sadaqah Nahdlatul Ulama (LAZIS-NU) is one of theNational Zakat amil institution that manages zakat, infaq shadaqah and ZISWAF).NU Care-LAZISNU has actually prepared a new flow of NU independencethrough the movement of the infaq box (KOIN NU). The KOIN NU movement is a movementnahdliyin to collect small change from houses. With the existence of NU COINScan be the main way, the main solution, the mainstay program to realize the new floweconomic independence of the archipelago. The number of NU residents is very large and averagecomes from a lower middle class economy, so it is based on a community alms can model